2011
DOI: 10.1182/blood-2011-01-329821
|View full text |Cite
|
Sign up to set email alerts
|

Chronic graft-versus-host disease: long-term results from a randomized trial on graft-versus-host disease prophylaxis with or without anti–T-cell globulin ATG-Fresenius

Abstract: Previous randomized graft-versus-host disease (GVHD)-prophylaxis trials have failed to demonstrate reduced incidence and severity of chronic GVHD (cGVHD).Here we reanalyzed and updated a randomized phase 3 trial comparing standard GVHD prophylaxis with or without pretransplantation ATG-Fresenius (ATG-F) in 201 adult patients receiving myeloablative conditioning before transplantation from unrelated donors. The cumulative incidence of extensive cGVHD after 3 years was 12.2% in the ATG-F group versus 45.0% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
210
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(238 citation statements)
references
References 47 publications
23
210
1
4
Order By: Relevance
“…The protective effect of ATG on chronic lung dysfunction has been demonstrated in prospective randomized trials. 30,31 Other authors have reported an association of extensive cGVHD with BOS. 3,32 However, cGVHD besides BOS and aGVHD, both of which were previously identified as a risk factors for BOS in heterogeneous groups of transplanted patients, 3,33 could not be shown to be significantly associated with BOS in our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of ATG on chronic lung dysfunction has been demonstrated in prospective randomized trials. 30,31 Other authors have reported an association of extensive cGVHD with BOS. 3,32 However, cGVHD besides BOS and aGVHD, both of which were previously identified as a risk factors for BOS in heterogeneous groups of transplanted patients, 3,33 could not be shown to be significantly associated with BOS in our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…How ATG, given peritransplant, prevents cGVHD, [13][14][15]20,31,44,45 which typically develops at X3 months post transplant, has been a mystery. The correlation between ATG and IL15 levels and the inverse correlation between IL15 levels and CD8 T-cell counts ( Figure 3) and the published inverse correlation between day 7 or 28 ATG levels and day 28 CD8 T-cell counts 37 suggest that ATG kills or prevents expansion of CD8 T cells, some of which (alloreactive CD8 T cells?)…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis of cGVHD using T-cell depletion ex vivo (for example, by graft enrichment for CD34 cells) or in vivo (for example, using alemtuzumab or polyclonal anti-T-cell antibodies like rabbit antithymocyte globulin (ATG)) is more efficacious than treatment. [9][10][11][12][13][14][15] However, the prophylaxis has side effects (for example, viral infections 16 ). Therefore, it would be desirable to give prophylaxis or preemptive therapy only to patients at high risk of developing cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] The link between ATG use and the decreased risk of cGvHD is not completely understood. There is evidence in mouse models that the thymus is damaged by prior chemotherapy, conditioning regimen, TBI, acute GvHD and age-related atrophy.…”
Section: Discussionmentioning
confidence: 99%